Perilaku CERDIK pada Keluarga Mahasiswa Keperawatan Politeknik Kesehatan Bhakti Mulia - Yuliyanti, Tutik (Indonesian Journal on Medical Science, 2024)
Nursing students play an important role in influencing healthy behavior in society, especially their families. Non-communicable disease are directly related to lifestyle, and should be managed by implementing healthier habits, namely CERDIK behavior (health checks, get rid of cigarette smoke, be diligent in physical activity, balanced diet, get enough rest, manage stress). The aim of this research is to describe CERDIK behavior in the families of Bhakti Mulia Health Polytecnic nursing students. The design of this research is descriptive analytic with frequency distribution dat analysis. The sampling technique was purposive sampling, namely 147 people using a measuring instrument using the CERDIK behavior questionnaire. The research results showed that : student families had CERDIK behavior with details:58,5% carried out routine health checks,84,4% got rid of cigarette, 77,6% diligent physical activity behavior, 77,6% had a balanced diet, 80,3% had enough rest,88,4% managed behavior stress. Suggestion: It is hoped that assistance with the needed so that people at risk of non-communicable disease receive good quality health.